Plate 06. View of Rüdesheim near Bingen - Janscha, Laurens, 1749-1812 (artist):::::::::::::::; Ziegler, Johann (engraver)::::::::::::::: (Edinburgh; Paul Harris; United Kingdom, 2020)
Color engraving of the village of Rüdesheim in Germany, near Bingen, on the Rhine